The Impact of the Tobacco-Free Policy on the AUC New Cairo Campus - Badawy, Fatimah (AUC Knowledge Fountain, 2023)
In 2019, the American University in Cairo (AUC) conducted a research study on campus attitudes towards tobacco use and smoking behaviors within their community, in light of the then newly enforced tobacco-free policy. They found most campus members in support of the policy, with higher rates of disapproval from the smoking community. In 2021, this research aimed to follow-up on changes in attitudes towards the policy as well was smoking behaviors. It hypothesized that over time, levels of support to the policy would increase, smoking habits would be positively impacted and that positive health behaviors would correlate with policy support. Student participants (n=101) were given a three-part survey consisting of: The Positive Health Behavior Scale (PHBS) which aimed to assess positive health behaviors, select items from the “Tobacco Use within the AUC Community ‘19” survey which measured levels of agreement with the policy, and an assessment of knowledge on policy stipulations. Two Tobacco Free Committee members and four student participants who attended the implementation were also interviewed to add richness to the data. The results showed a significant increase in agreement with the policy. However, there was a significant drop in agreement on an item asking if people follow the policy, and on an item asking if the size of the smoking areas was adequate. No correlation was found between positive health behaviors and levels of agreement with the policy. Over half of smoking participants also reported smoking less after the policy’s implementation. The interviews reflected themes revolving around the agreement to the policy’s intent and stipulations along with complaints about administration’s methods of communication of the policy. This research concluded that the tobacco-free policy had an overall successful and positive impact on AUC campus.